2004
DOI: 10.1158/1078-0432.ccr-03-0611
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Type II Transforming Growth Factor-β Receptor Inhibits Established Murine Malignant Mesothelioma Tumor Growth by Augmenting Host Antitumor Immunity

Abstract: Purpose: Transforming growth factor (TGF)-␤ blockade has been proposed as an anticancer therapy; however, understanding which tumor patients might benefit most from such therapy is crucial. An ideal target of such inhibitory therapy might be malignant mesothelioma (MM), a highly lethal, treatment-resistant malignancy of mesothelial cells of the pleura and peritoneum that produces large amounts of TGF-␤. The purpose of this study was to explore the possible therapeutic utility of TGF-␤ blockade on MM.Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 51 publications
5
55
2
2
Order By: Relevance
“…We further showed that IL-17 could directly promote survival of 4T1 tumor cells, both in vitro and in vivo, thus providing a plausible explanation for the tumor-promoting effect of CD8+ T cells in this model. Many tumors are already known to evade immune surveillance by compromising the development or activity of tumor-specific cytotoxic T-cells, often in a TGF-h-dependent manner (3,15,16,19,37,42,43). However, our data suggest that some tumors may go further, creating a local cytokine environment that actively skews local differentiation or expansion of CD8+ T cells to a state where they directly promote tumor growth.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We further showed that IL-17 could directly promote survival of 4T1 tumor cells, both in vitro and in vivo, thus providing a plausible explanation for the tumor-promoting effect of CD8+ T cells in this model. Many tumors are already known to evade immune surveillance by compromising the development or activity of tumor-specific cytotoxic T-cells, often in a TGF-h-dependent manner (3,15,16,19,37,42,43). However, our data suggest that some tumors may go further, creating a local cytokine environment that actively skews local differentiation or expansion of CD8+ T cells to a state where they directly promote tumor growth.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, immunoregulatory cells, such as T regs and NKT cells may either make or induce production of TGF-h (14,15). Furthermore, there is a growing body of data suggesting that strategies to antagonize TGF-h can suppress tumorigenesis by enhancing or restoring effective antitumor immune surveillance (15)(16)(17)(18)(19)(20)(21), thus underscoring the potential relevance of this mechanism to carcinogenic progression.…”
Section: Introductionmentioning
confidence: 99%
“…CD8 + T cells were responsible for tumour cell killing following treatment, but were less efficient in bulky TGF- secreting tumours. Furthermore, complete regressions were not observed (Suzuki et al, 2004).…”
Section: Other Strategiesmentioning
confidence: 96%
“…TGF-β has received attention as a therapeutic target based on in vivo studies that demonstrated blocking of TGF-β by neutralizing antibodies, TGF inhibitors and other methods resulted in MM tumor inhibition (Marzo et al, 1997;Suzuki et al, 2004;. A phase II clinical trial investigating the use of an anti-TGF monoclonal antibody, GC1008, in relapsed MPM patients is in progress.…”
Section: Experimental Therapy Of Malignant Mesotheliomamentioning
confidence: 99%